Upaya Meningkatkan Efektivitas Bhabinkamtibmas Dalam Menangani Tindak Pidana Curanmor Di Wilayah Hukum Polres Jakarta Barat - Austin Junior; Ade Adhari (UNES Law Review, 2023)
Improving the effectiveness of Bhabinkamtibmas in handling motorcycle theft in the jurisdiction of West Jakarta Police Resort requires a holistic approach and synergy among the police, the community, and other relevant stakeholders. By implementing the above strategies, it is hoped that a safer environment can be created, free from motorcycle theft crimes. The research methodology employed in this study is descriptive analysis, which depicts the symptoms and facts observed by the author in the field related to the existing issues. The research findings indicate that efforts to enhance the effectiveness of Bhabinkamtibmas in addressing motorcycle theft in the jurisdiction of West Jakarta Police Resort involve several strategic steps. These include enhancing the skills of Bhabinkamtibmas, strengthening collaboration with local communities, utilizing information technology, conducting regular patrols, providing education to the community, empowering the human resources of Bhabinkamtibmas, and evaluating performance. With this holistic approach, it is expected to create a safer environment and reduce cases of motorcycle theft in the area.